Factors Affecting the Intention to International Course in Business Administration Programs, Savannakhet University - MANIVONG, Khamkeo; TOUNMANYSONE, Thongsa; VONGKHASEUM, Bounphan (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to: 1) determine the level of intention to the International Course in Business Administration program at the Faculty of Business Administration, Savannakhet University; and 2) identify factors affecting this intent at the Faculty of Business Administration, Savannakhet University. The researcher used cross-sectional data collected from a sample of 1,126 people. in Kaysone Phomvihane City, Uthoumphone District, Atsaphangthong and Songkhon. Statistical analyses included the mean, standard deviation, and a two-option economic logit model. The findings indicate that demand for the international business administration program is high, with a mean score of 3.76 (S.D. = 0.59). Factors influencing the desire for admission include the father's and mother's occupations, career expectations after graduation, social status, and the institution's image.